Recent Advances in the Recognition and Management of Eosinophilic Esophagitis - Gregory Eustace; Xianyong Gui; Marietta Iacucci (Canadian Journal of Gastroenterology and Hepatology)
The incidence and recognition of eosinophilic esophagitis is increasing. Pathophysiological understanding of eosinophilic esophagitis is improving and an immunological reaction to ingested food is likely to play a significant role. Patients present with dysphagia and food bolus obstruction. Both histological and endoscopic criteria have been developed and validated. Dietary therapy, topical steroid therapy, proton pump inhibitors and endoscopic dilation are the main approaches to therapy; however, novel targeted therapies are being developed. Among the food items commonly implicated are wheat, dairy, nuts, soy, shellfish and eggs. A multidisciplinary approach to management in dedicated clinics may yield the best results.